The Girl in the Labyrinth - Adaviruku, Wafikah (Nigeria, 2022)
Oyazi couldn't stand by and watch the orphanage marry her off to an unknown man to hide the truth of her pregnancy. She knew life was more the four walls of the orphanage, and she was determined to see it. On the night she flees the orphanage, a chance encounter gets her adopted by a wealthy family, introducing her to a life of luxury she only ever saw in her dreams...
Keywords: Juvenile Fiction